Daptomycin Versus Vancomycin for Bloodstream Infections Due to Methicillin-Resistant Staphylococcus aureus With a High Vancomycin Minimum Inhibitory Concentration: A Case-Control Study - Moore, Carol L.; Osaki-Kiyan, Paola; Haque, Nadia Z.; Perri, Mary Beth; Donabedian, Susan; Zervos, Marcus J. (Clinical infectious diseases, 2012)
Background. Reports have found a link between vancomycin treatment failure in methicillin-resistant Staphyloccocus aureus (MRSA) bloodstream infections (BSIs) and higher vancomycin minimum inhibitory concentrations (MICs), despite MICs being below the susceptibility breakpoint of 2 µg/mL. Consensus guidelines recommend considering use of alternative agents for infections involving a higher vancomycin MIC, despite few data to support this approach. Methods. This retrospective case-control study evaluated the effectiveness and safety of vancomycin, compared with that of daptomycin, in the treatment of MRSA BSIs with a high vancomycin MIC (ie, > 1 µg/mL). Results. A total of 118 vancomycin-treated subjects were compared with 59 daptomycin-treated subjects. Clinical failure, defined compositely as mortality, microbiologie failure, and/or recurrence of infection, was numerically lower in daptomycin-treated subjects (31% vs 17%; P = .084) and was mainly driven by a lower incidence of mortality in the daptomycin group (20% vs 9%; P = .046). Factors independently associated with clinical failure included acute renal failure (odds ratio [OR], 3.91 [95% confidence interval CI, 1.05-14.56]) and vancomycin treatment group (OR, 3.13 [95%, CI, 1.00-9.76]). Right-sided endocarditis was independently associated with clinical success (OR, 0.07 [95% CI, .01-. 83]). A comparison of 60-day mortality between vancomycin-and daptomycin-treated subjects found a higher probability of survival in the daptomycin-treated group (P = .022). Conclusions. The results demonstrated that daptomycin was associated with a better outcome compared with vancomycin for the treatment of BSIs due to MRSA with higher vancomycin MICs. These findings support the recommendations of recent guidelines, which suggest consideration of the switch to alternative agents when the isolate has a high vancomycin MIC or when patients are not improving during receipt of therapy.